The Sacral and the Profane in the Space of Festive Culture - Litvinova, M.V.; Vereitinova, T.Y. (International Journal of Criminology and Sociology, 2022)
The problem of the study of “sacral” and “profane” in the discourse of the philosophy of culture has repeatedly been raised in numerous works of foreign and domestic authors. The fundamental development of the concepts of “sacral” and “profane” opens up grand-scale opportunities for the study of various forms of culture through the prism of the theory of “sacral”. The oldest collective form of culture that is extant to this day is the festivity, at the base of which there are “sacral” / “sacred” values and the truths of a particular society, no matter what type and era it belongs to. Modern socio-philosophical and cultural problems that arose at the beginning of the 20th century led to the emergence of value disorientation of several generations of people, which, in turn, has been leading modern society to even larger problems in all areas and directions of modern civilization. The major purpose of the study is to analyze and determine the interest and relevance to the study of the holiday as a mirror of the era, reflecting the images of the sacral and the profane in the culture of the people, their real aspirations, ideals, values and their consequences.